IL-6 and other biomarkers as predictors of severity in COVID-19. (1st January 2021) - Broman, N.; Rantasärkkä, K.; Feuth, T.; Valtonen, M.; Waris, M.; Hohenthal, U.; Rintala, E.; Karlsson, A.; Marttila, H.; Peltola, V.; Vuorinen, T.; Oksi, J.
Abstract: Objective: Cytokine release syndrome is suggested to be the most important mechanism triggering acute respiratory distress syndrome and end organ damage in COVID-19. The severity of disease may be measured by different biomarkers. Methods: We studied markers of inflammation and coagulation as recorded in 29 patients on admission to the hospital in order to identify markers of severe COVID-19 and need of ICU. Results: Patients who were eventually admitted to ICU displayed significantly higher serum levels of interleukin-6 (IL-6), C-reactive protein (CRP), and procalcitonin. No statistical differences were found between the groups in median levels of lymphocytes, D-dimer or ferritin. Conclusions: IL-6 and CRP were the strongest predictors of severity in hospitalized patients with COVID-19.